Robotic-Assisted Surgery Systems and Their Clinical Outcomes: A Digital Health Perspective - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Robotic-Assisted Surgery Systems and Their Clinical Outcomes: A Digital Health Perspective The integration of robotics and artificial intelligence (AI) ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning